Workplace violence towards healthcare workers: an observational study in the College of Physicians and Surgeons of Rome - Marte, Mattia; Cappellano, Ernesto; Sestili, Cristina; Mannocci, Alice; La Torre, Giuseppe (La Medicina del Lavoro, 2019)
Introduction: Aggressions to healthcare personnel are a growing and underestimated phenomenon. The damage to the individual and to the community is real, since the assaults increase work stress and can also lead to sickness absence. Moreover, the consequences on the quality of care and economic repercussions need to be taken into account. Objective: To estimate the prevalence of violence towards medical personnel of the College of Physicians and Surgeons of Rome and to evaluate its association with socio-demographic variables. Methods: Cross-sectional study. Respondents completed an online questionnaire composed of 30 questions on personal information, work, any aggression suffered and opinions about the phenomenon. Descriptive statistical analysis, univariate, bivariate and multivariate analyses were performed. Results: Out of 956 responders, 66.5% experienced at least one episode of aggression during their working life. Women were more likely victims than men (71%), especially due to verbal aggression (OR 1.53, 95%CI: 1.16-2.02). Age acts as a protective factor (OR 0.97; 95%CI: 0.96-0.99). The subjects with a full time position (OR 2.1; 95%CI: 1.46-3.05) seem to be more at risk. In addition, the doctors employed in the territorial structures of the National Health System (OR 2.08; 95%CI: 1.36-3.18), as well as in the local emergency services (OR 3.39; 95%CI: 1.14-10.05) and in social security institutions (OR 9.58; 95%CI:1.2-76.41) were more at risk. Conclusions: The results of this study reveal that the phenomenon of aggression is not negligible, and that awareness on the issue and staff training is essential.